Pembuatan Media Pembelajaran Dasar Kreatifitas Berbasis Android (Studi Kasus Kelas X SMK Negeri 7 Padang) - Ita Roza; M Menrisal; Yuliawati Yunus (Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to determine the effectiveness of Android-based learning media on basic creativity learning subjects at SMK Negeri 7 Padang. This study uses research & development methods. The research subjects were 35 students of the Department of Dance. This study uses a development model (ADDIE model), with the development steps as follows. (1) Analyze, (2) Design, (3) Development, (4) Implementation and (5) Evaluate. The results of the assessment of the effectiveness test of 87.20% can be interpreted as Very Effective, The results of the assessment of the practicality test are 88.57%, can be interpreted as Very Practical to use. The results of the assessment of the effectiveness test of 87.20% can be interpreted as Very Effective to use. In conclusion, based on the assessment and expert input as well as the results of the field trial of the Android-Based Learning Media Application as a learning medium, it has been tested for its feasibility, excellence, and can be used in the learning process in the Basic Creativity subject for class X SMK N 7 Padang